(untitled) (International Journal of Current Engineering and Technology, 2014)
The burgeoning urban population of India with rapid rise in industrialization coupled with high increase of road vehicles engaging in rapidly expanding cities to fit the developmental needs of the economy demands good quality of roads to cope up the increasing pressure of road traffic. It becomes the responsibility of researchers, scientists, contractors to improve the riding quality while maintaining the economy for the country like ours. In this paper, initially the investigations are carried out to determine engineering properties of locally available crushed stones, fillers and 60/70 grade bitumen for mix design. Marshall Method of mix design for DBM (grade 1) was adopted to find out the optimum bitumen content. In order to arrive at homogenous mix with required standards, VG 30 bituminous mix with obtained 4.25% optimum bitumen content is taken into consideration for Modified Marshall Mix design by addition of 0.03%, 0.04% and 0.06% dosage of zycosoil chemical is prepared and tested to determine the key properties as per the codal provision. The tests indicated the desire to opt for chemically modified DBM mix is it shows better results as compared to conventional mix hence it is suggested to use for the construction of Flexible pavement.